Consequences Of Digital Divides: How Internet Use Affects Social Well-Being - Büchi, Moritz; Festic, Noemi; Latzer, Micheal (AoIR Selected Papers of Internet Research, 2017)
With the diffusion of the Internet in modern societies came a plethora of research on differences in Internet access (first-level digital divides) and use (second-level digital divides), but the consequences of these digital divides remain largely unclear. This paper argues that social integration and subjective well-being are a key outcome to consider and contain potential as the object and basis of public digital-information policies. How do Internet skills and different usage types affect individuals’ social well-being? The study uses nationally representative survey data from Switzerland (_N_=1121) collected in 2015 to address this research question. Structural equation modeling was used to test the effects of three different types of Internet use, Internet skills, and feelings of belongingness to the information society on social well-being, while controlling for sociodemographic variables. The preliminary results show that Internet use for informational, entertainment, or social purposes, as well as Internet skills, do not have a direct effect on social well-being. However, the perception of belongingness to the information society—which significantly depends on Internet skills and Internet use for informational purposes—positively predicts social well-being. Further analysis of the data will focus on generational differences as well as on non-users of the Internet. The results of this study illustrate the consequences of existing digital divides and have broad policy implications since they contribute to the empirical basis of evidence-based policy-making regarding the promotion of Internet use and digital skills development.